Correlation of iCare ic100 tonometry with iCare TA01i in screening of unselected population in Northern Finland Birth Cohort Eye study. Issue 2 (March 2022) - Liinamaa, M Johanna; Stoor, Katri; Leiviskä, Ilmari; Saarela, Ville
Purpose: iCare tonometers are easy-to-use and portable devices for measuring the intraocular pressure (IOP). Purpose was to evaluate the IOP values measured by both novel iCare ic100 and conventional model TA01i devices in unselected population. Methods: IOP was measured with iCare ic100 and TA01i tonometers in 149 participants aged 32–33 years (born in 1985 or 1986) of the Northern Finland Birth Cohort Eye 2 study. The right eye of each participant was selected for analysis. We also collected data on axial length, corneal curvature and central corneal thickness (CCT). Bland-Altman plot was used for comparing the values obtained by these devices. Results: Mean IOP measured with the ic100 device was 13.8 (3.4) mmHg, with TA01i it was 12.5 (3.0) mmHg. The mean difference between these devices was 1.30 mmHg ( p < 0.001) and R 2 was 0.694. In Bland-Altman analysis, the agreement between the two tonometers ic100 and TA01i was constantly good (mean difference −1.30, ic100 device showing higher measures). There was a correlation between IOP and CCT ( r = 0.269, p < 0.001 for ic100 and r = 0.255, p = 0.002 for TA01i), but not with IOP and corneal curvature or IOP and axial length. Conclusion: In summary, we found ic100 rebound tonometry to be both reliable and effective, although CCT may influence IOP measurements with ic100 and TA01i. Therefore, iCare ic100 is suitable for IOP measurement in large cohort studies.